Pengaruh Zakat Produktif, Manajemen Usaha, dan Pendampingan Terhadap Perkembangan Usaha Mikro Mustahik di LAZNAS LMI Unit Layanan Blitar - Kurniawan, Moh. Zaki; Ula, Muhammad Fathul; Setyawan, Aris (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2020)
This study aims to determine the effect of productive zakat, business management, mentoring on the development of micro-businesses in LAZNAS LMI Blitar Service Unit. The research population consisted of 67 mustahik people in the economic empowerment program at LAZNAS LMI Blitar Service Unit. The samples taken were 57 people based on simple random sampling technique. The results of the study using multiple linear regression indicate that there is a positive and significant effect both partially and simultaneously between productive zakat, business management, and mentoring on the development of mustahik micro businesses.